ANALISIS PENGARUH UTANG LUAR NEGERI, BI RATE, NET EKSPOR DAN KURS TERHADAP CADANGAN DEVISA INDONESIA - Vanesza Natasha Immanuella Maria Gloria Situmorang, (2022)
As one of the basic indicators for a country to support the economy, foreign exchange reserves must be maintained to remain stable. In keeping foreign exchange reserves safe, several policies are directed at keeping the economy healthy and strong, such as using foreign debt wisely, encouraging exports and managing imports, as well as supporting market stability and the exchange rate. The purpose of this study was to determine the effect of foreign debt, BI rate, net exports and the exchange rate on Indonesia's foreign exchange reserves. The research sample was taken from 1990-2019 as many as 30 data. The econometric tool used to perform this quantitative analysis is Eviews 10 by using multiple linear regression analysis on time series data. The data are collected from the publications of the Central Statistics Agency and the World Bank. The results show that (1) foreign debt has a positive and significant effect on Indonesia's foreign exchange reserves, (2) the BI rate has a negative and significant effect on Indonesia's foreign exchange reserves, (3) net exports have no significant effect on Indonesia's foreign exchange reserves, (4) the exchange rate does not have a significant effect on Indonesia's foreign exchange reserves. Simultaneously, foreign debt, BI rate, net exports and the exchange rate have a significant influence on Indonesia's foreign exchange reserves.